Digitization in the Market for Entrepreneurial Finance: Innovative Business Models and New Financing Channels. (September 2022) - Bertoni, Fabio; Bonini, Stefano; Capizzi, Vincenzo; Colombo, Massimo G.; Manigart, Sophie
Digitization creates new financial channels that complement traditional intermediaries, but may raise concerns over fraud, cybersecurity, or bubbles. Artificial intelligence and machine learning change the way in which traditional investors work. This special issue focuses on economic, cultural, and regulatory determinants of fintech development, and on the new forms of information production and processing engendered by digital entrepreneurial finance. We provide a general overview of digitization in the market for entrepreneurial finance, illustrate how the different articles in the special issue contribute to advance our knowledge, and identify promising avenues for research.